2023
DOI: 10.1111/grow.12673
|View full text |Cite
|
Sign up to set email alerts
|

Building innovative capacity in regional entrepreneurship and innovation (eco)systems: Startups versus incumbent firms

Abstract: This article studies how three sets of regional factors—knowledge, agglomeration, and openness—impact and interact differently with startups and incumbent firms in their innovative capacity building. Based on a large dataset of Chinese high‐tech firms, regression analysis shows that the speed of growing startup innovative capacity relies positively on regional knowledge stock and localization economies. In addition to regional knowledge stock, incumbent innovative capacity building benefits from urbanization e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…For instance, recently, ref. [55] associated various regional factors like existing regional knowledge stock, agglomeration economies, urbanization economies, and regional openness with innovative capacity building in start-ups, respectively, incumbent firms. The authors reported a positive relationship between regional factors and innovation capacity development.…”
Section: Regional and Urban Economics Perspectivementioning
confidence: 99%
“…For instance, recently, ref. [55] associated various regional factors like existing regional knowledge stock, agglomeration economies, urbanization economies, and regional openness with innovative capacity building in start-ups, respectively, incumbent firms. The authors reported a positive relationship between regional factors and innovation capacity development.…”
Section: Regional and Urban Economics Perspectivementioning
confidence: 99%